2022
DOI: 10.1186/s41983-022-00513-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of anxiety in patients with epilepsy during COVID-19 pandemic

Abstract: Background Epilepsy is one of the most frequent and serious brain disorders. The nature of the disorder and the unpredictability of seizures usually puts patients in a state of apprehension and anticipation, which creates a continuous condition of anxiety. COVID-19 pandemic has created a state of generalized anxiety all over the world. It is expected that patients with epilepsy (PWE) will suffer from more anxiety during the pandemic. This cross-sectional study was applied on 290 PWE. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…Similarly to our results, McKenzie et al showed that pessimism and worthlessness were highly correlated with major depression among hospitalized, medically ill patients [ 55 ]. Additionally, in line with previous research [ 21 , 51 , 56 ], patients with high illness apprehension displayed a significantly greater level of anxiety. Our study thus extends the results of prior research conducted among general and specific subgroups of inpatients, suggesting their relevance among all Lebanese inpatients regardless of disease type and severity.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly to our results, McKenzie et al showed that pessimism and worthlessness were highly correlated with major depression among hospitalized, medically ill patients [ 55 ]. Additionally, in line with previous research [ 21 , 51 , 56 ], patients with high illness apprehension displayed a significantly greater level of anxiety. Our study thus extends the results of prior research conducted among general and specific subgroups of inpatients, suggesting their relevance among all Lebanese inpatients regardless of disease type and severity.…”
Section: Discussionsupporting
confidence: 89%
“…The effect of pandemic precautions on patients’ jobs, low financial status, fear of infection and death by COVID-19, fear of job loss, increased seizures rate during pandemic, increased ER visits, and lack of drug adherence during the pandemic, were significantly associated with increased risk of anxiety and depression. One study reported a rate of anxiety as high as 52.4% in PWEs as compared to a pre-pandemic rate of 20.2% ( 31 , 32 ). Other studies found depression rates ranging from 39% to 47% in PWEs during the pandemic as compared to a pre-pandemic rate of 22.9% ( 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%